Research Status of Ultra-low Temperature Pressure Vessel Steel - Cao Lujun, Zhou Yucheng, Sun Shihao, Hu Jikang (Teshugang)
Steel for ultra-low-temperature pressure vessel is steel specifically applied to liquid nitrogen （-196 ℃） and below， and requiring sufficient mechanical strength and toughness under extreme low-temperature conditions. In general， the strength and hardness of steels increase as the temperature decreases， but at the same time this is accompanied by a significant increase in the risk of brittle fracture and a decrease in plastic deformability， creating significant difficulties and challenges in their design and application. Based on the demand for high strength and toughness of ultra-low-temperature pressure vessels at temperature of -196 ℃ and below， and in response to the bottleneck problem that it is difficult to combine high toughness and high strength of steel at ultra-low temperatures， the performance characteristics of steel in ultra-low-temperature environments are introduced from the classification of steel and the current status of the research， respectively. In addition， new methods， processes and research and development progress of steel toughening in ultra-low-temperature environments are summarized， focusing on the analysis of low-temperature toughness mechanisms and strengthening strategies of several typical ultra-low-temperature steels， as well as their tough-brittle transition mechanisms， which mainly include martensitic phase transformation， dislocation motion and twin crystal formation and other micro-mechanisms. The effects of factors such as chemical composition， crystal structure and grain size on the low-temperature toughness of steel are summarized. Finally， based on the existing research results， the preparation and strengthening of steels for ultra-low-temperature pressure vessels are prospected.